2005
DOI: 10.4049/jimmunol.174.5.2563
|View full text |Cite
|
Sign up to set email alerts
|

The Fate of Low Affinity Tumor-Specific CD8+ T Cells in Tumor-Bearing Mice

Abstract: A major challenge in tumor immunology is how best to activate the relatively low avidity self-specific and tumor-specific T cells that are available in the self-tolerant repertoire. To address this issue, we produced a TCR transgenic mouse expressing a class I-restricted hemagglutinin (HA)-specific TCR (clone 1 TCR) derived from a mouse that expressed HA as a self-Ag in the insulin-producing β cells of the pancreatic islets (InsHA) mice. Upon transfer of clone 1 TCR CD8+ T cells into InsHA mice, very few cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
0

Year Published

2005
2005
2011
2011

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 53 publications
3
56
0
Order By: Relevance
“…It remains possible that prolonged exposure to endogenous Tag renders TCR-V cells destined for future deletion because these cells are not retained at detectable levels unless the mice are immunized. Similar observations have been made with TCR-transgenic T cells responding to immunodominant tumor epitopes upon transfer into tumor-bearing mice (34,47,57). Our findings here using TCR-transgenic T cells imply that higher avidity endogenous epitope V specific T CD8 that survive negative selection in SV11 mice might additionally be subject to tolerance upon recognition of and activation by persistent Tag in the peripheral tissues, thereby contributing to the low levels of functional epitope V-specific T cells available for recruitment in tumor-bearing mice (17).…”
Section: Discussionsupporting
confidence: 61%
See 2 more Smart Citations
“…It remains possible that prolonged exposure to endogenous Tag renders TCR-V cells destined for future deletion because these cells are not retained at detectable levels unless the mice are immunized. Similar observations have been made with TCR-transgenic T cells responding to immunodominant tumor epitopes upon transfer into tumor-bearing mice (34,47,57). Our findings here using TCR-transgenic T cells imply that higher avidity endogenous epitope V specific T CD8 that survive negative selection in SV11 mice might additionally be subject to tolerance upon recognition of and activation by persistent Tag in the peripheral tissues, thereby contributing to the low levels of functional epitope V-specific T cells available for recruitment in tumor-bearing mice (17).…”
Section: Discussionsupporting
confidence: 61%
“…These studies were primarily performed using transplantable tumors that expressed foreign Ag. By contrast, it has been reported that under tolerizing conditions, immunodominant self-epitope specific T CD8 do not readily penetrate transplanted tumors that express self-Ag (34,47). Our results show that in the context of self-Ag expression, functionally competent Tag-V-specific T cells accumulate within the tumor, indicative of specific recognition of this epitope in vivo.…”
Section: Discussionmentioning
confidence: 38%
See 1 more Smart Citation
“…The most effective antitumor response will likely be generated by enhancing low-affinity anti-HER-2/neu-specific CD8 ϩ T cells that were not deleted during thymic selection (46). This will be particularly important in transgenic mouse models of cancer in which the mice are tolerant to the tumor Ag and the high-affinity T cells that can be generated to target the tumor in wild-type (nontolerant) mice will not be present (47,48).…”
Section: Discussionmentioning
confidence: 99%
“…Clone 1 (CL1) CD8 T cells are also HA specific, but the T cell receptor (TCR) expressed by these cells was originally isolated from a mouse expressing HA in the pancreas and exhibits low affinity for HA (3). It would be expected that such low-avidity CD8 cells would more closely reflect what is available for tumor eradication in the endogenous repertoire.…”
Section: Il-2 and Il-15 Complexes Enhance Activation Of Naïve Cd8 T Cmentioning
confidence: 99%